Is fiscal consolidation self-defeating? A Panel-VAR analysis for the Euro area countries - Maria Grazia Attinasi; Luca Metelli (European Central Bank (ECB), 2016)
This paper studies the effects of fiscal consolidation on the debt-to-GDP ratio of 11 Euro area countries. Using a quarterly fiscal Panel VAR allows us to trace out the dynamics of the debt-to-GDP ratio following a fiscal shock and to disentangle the main channels through which fiscal consolidation affects the debt ratio. We define a fiscal consolidation episode as self-defeating if the debt-to-GDP ratio does not decrease compared to the pre-shock level. Our main finding is that when consolidation is implemented via a cut in government primary spending, the debt ratio, after an initial increase, falls to below its pre-shock level. When instead the consolidation is implemented via an increase in government revenues, the initial increase in the debt ratio is stronger and, eventually, the debt ratio reverts to its pre-shock level, resulting in what we call self-defeating austerity.
Keywords: E62; H6; C33; 330; debt trajectory; fiscal consolidation; fiscal stress; panel VAR